Oral manifestations in patients with COVID-19 - Quispe Vargas, Yessica del Rocio (2021)
The severe acute respiratory syndrome type 2 coronavirus (SARS-Cov-2) the causative agent of COVID-19, is found in saliva in a large percentage and saliva plays an important  role as a transmitter of SARS-Cov-2 infection. Therefore, the oral cavity could be a reservoir for SARS-Cov-2 virus due to the hight affinity of this virus for cells with receptors for angiotensin-converting enzyme (ACE 2) and sialic acid, thus affecting the functioning of the salivary glands, taste sensations, smell andthe integrity  of the muco oral. Clinical manifestations have been reported among signs and symtoms that have contributed to understand the behavior of this SARS- Cov-2 virus; of wich dysgeusia, ageusia, hipogeusia and dry mouth have been reported in a large percentage among the main oral manifestation; however, there is a lack of information regarding oral manifestations in patients with COVID-19. The aim of this review is to identify the possible oral manifestations in patients with COVID-19 by compiling the information and presenting an uptaded presentation of the literature.